Ways of implementing green spaces in urban areas based on selected market revitalisation projects in Greater Poland - Tomczak, Karol (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2025)
The aim of the article is to present ways of reintroducing and enhancing greenery in urban spaces. Many revitalisation activities in markets and squares have resulted in the loss of their attractiveness. Removal of greenery elements led to a deepening degradation of spaces and intensification of urban heat islands. The introduction of new revitalisation guidelines for local governments forced a change in the approach to ongoing projects. The investments undertaken should preserve historic tree cover and limit the design of paved surfaces at the expense of existing vegetation. With the current climatic conditions, special emphasis is placed on the condition of the natural environment in urbanised spaces. In order to identify design trends, we selected markets in Greater Poland, where revitalisation efforts have been undertaken in recent years. Places were selected for the study, in which existing greenery was preserved or supplemented with new plantings. A comparative analysis of implementation and planned revitalisation projects in relation to the status quo was carried out.